Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s12871-015-0053-5
|View full text |Cite
|
Sign up to set email alerts
|

Ringer’s lactate, but not hydroxyethyl starch, prolongs the food intolerance time after major abdominal surgery; an open-labelled clinical trial

Abstract: BackgroundThe infusion of large amounts of Ringer’s lactate prolongs the functional gastrointestinal recovery time and increases the number of complications after open abdominal surgery. We performed an open-labelled clinical trial to determine whether hydroxyethyl starch or Ringer’s lactate exerts these adverse effects when the surgery is performed by laparoscopy.MethodsEighty-eight patients scheduled for major abdominal cancer surgery (83% by laparoscopy) received a first-line fluid treatment with 9 ml/kg of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Adverse effects of crystalloids are associated with their preferential distribution to the subcutis, gut, and lungs. When more than 2 L is administered, the gastrointestinal recovery time is delayed by 2 days [76]. Infusion of even larger amounts of crystalloids during open abdominal surgery causes impaired wound healing, pulmonary edema, pneumonia, and pitting edema in the leg [53,54].…”
Section: Adverse Effects Of Fluidsmentioning
confidence: 99%
“…Adverse effects of crystalloids are associated with their preferential distribution to the subcutis, gut, and lungs. When more than 2 L is administered, the gastrointestinal recovery time is delayed by 2 days [76]. Infusion of even larger amounts of crystalloids during open abdominal surgery causes impaired wound healing, pulmonary edema, pneumonia, and pitting edema in the leg [53,54].…”
Section: Adverse Effects Of Fluidsmentioning
confidence: 99%
“…Anesthesiologists select the appropriate fluid type for the patient and administer the appropriate amount of fluid. Previous studies have shown that the type of fluid therapy is associated with postoperative recovery and prognosis [1][2][3][4]. For successful fluid therapy, it is helpful to quantify how the administered fluid is distributed and eliminated from the body.…”
Section: Introductionmentioning
confidence: 99%
“…The first clinical consequence when administrating more than 2 litres of fluid is a delay in the gastrointestinal recovery time of 2 days [9]. However, the total number of postoperative complications still seems to be lowest when providing between 1.75 and 2.75 L of crystalloid fluid during open abdominal surgery [10].…”
Section: Adverse Effects Of Crystalloid Fluidsmentioning
confidence: 99%